2015
DOI: 10.2141/jpsa.0150034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Enrichment on the Behavior and Welfare of Japanese Broilers at a Commercial Farm

Abstract: The effect of hay bales and perches as environmental enrichment material was investigated on the behavior, heterophil/lymphocyte (H/L) ratio, footpad dermatitis (FPD), and productivity of Japanese broilers in a commercial farm. About 21,500 birds were allocated to 4 houses: male versus female×control versus treatment house. We observed maintenance behavior, the utilization of hay bales and perches, and the H/L ratio of birds at 3, 5, and 8 weeks of age. FPD was scored and productivity was calculated at about 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 34 publications
6
34
3
2
Order By: Relevance
“…FCR was slightly improved, but mortality was also elevated. This result contradicts the findings of Ohara et al [6], who found a positive enrichment effect of straw bales and perches on FPD in female birds, but not males. No separate analysis by sex was undertaken in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…FCR was slightly improved, but mortality was also elevated. This result contradicts the findings of Ohara et al [6], who found a positive enrichment effect of straw bales and perches on FPD in female birds, but not males. No separate analysis by sex was undertaken in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…To address these welfare problems some recent studies have examined the possibility of improving leg health by increasing bird activity by means of providing environmental enrichment. Examples of types of environmental enrichment tested include the provision of perches [4][5][6], placing hay or straw bales into housing [7,8], introduction of sand trays, vegetable materials, hanging objects [5], a dust-bathing substrate, and mirrors [8,9]. All of these enrichments involve changing the nature of the rearing environment to increase its complexity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity increases both the thickness and density of the cortical bone and the diameter of the tibiotarsus diaphysis. The extent depends on the level of activity [32]. This deleterious effect of stocking density and age on locomotion has been observed previously [37,38].…”
Section: Effects On Behavioursupporting
confidence: 65%
“…It was not possible to complete the intended observation in week 6, since some animals exceed 3 kg of body weight and started to show mild signs of leg disorders. Video recording was used to crosscheck the behaviour at 10 min intervals and increase the accuracy of the counts [19,31,32]. The sole observer was blind to all aspects of treatments and intraobserver reliability, expressed as Pearson correlation coefficient, was 0.99 [30].…”
Section: Groomingmentioning
confidence: 99%